FUNCTION OF LANGUAGE IN PRESERVATION OF NATIONAL ETHNO-CULTURAL INFORMATION (on the example of materials of the Kazakh language) - Adilova Gulshat Agytaevna (Journals Park Publishing, 2023)
The article discusses the new directions of language research in modern world language education. Linguistics and ethnolinguistics in Kazakh linguistics have been studied with the formation of new trends. Cumulative measures of language in new linguistic fields are shown by examples.
Keywords: The relationship between language and culture, linguoculturology, spiritual culture, ethnolinguistics, etnogrographism, cumulative function of language.